Temporal Characteristics of Visual Processing in Amblyopia - Hu, Xia; Qin, Yi; Ying, Xiaoxiao; Yuan, Junli; Cui, Rong; Ruan, Xiaowei; He, Xianghang; Lu, Zhong-Lin; Lu, Fan; Hou, Fang (Frontiers in Neuroscience, 2021)
Purpose Amblyopia affects not only spatial vision but also temporal vision. In this study, we aim to investigate temporal processing deficits in amblyopia. Methods Twenty amblyopic patients (age: 27.0 ± 5.53 years, 15 males), and 25 normal observers (age: 25.6 ± 4.03 years, 15 males) were recruited in this study. Contrast thresholds in an orientation discrimination task in five target-mask stimulus onset asynchronies (SOA) conditions (16.7 ms, 33.4 ms, 50.0 ms, 83.4 ms, and ∞/no noise) were measured. An elaborated perceptual template model (ePTM) was fit to the behavioral data to derive the temporal profile of visual processing for each participant. Results There were significant threshold differences between the amblyopic and normal eyes [F(1,43) = 10.6, p = 0.002] and a significant group × SOA interaction [F(2.75,118) = 4.98, p = 0.004], suggesting different temporal processing between the two groups. The ePTM fitted the data well (χ2 test, all ps > 0.50). Compared to the normal eye, the amblyopic eye had a lower template gain (p = 0.046), and a temporal window with lower peak and broader width (all ps < 0.05). No significant correlation was found between the observed temporal deficits and visual acuity in amblyopia (ps > 0.50). Similar results were found in the anisometropic amblyopia subgroup. No significant difference was found between the fellow eyes of the monocular amblyopia and the normal eyes. Conclusion Amblyopia is less efficient in processing dynamic visual stimuli. The temporal deficits in amblyopia, represented by a flattened temporal window, are likely independent of spatial vision deficits.